The care economy and the state in Africa’s Covid-19 responses - Ossome, Lyn (Canadian Journal of Development Studies, 2021)
The responses of many low- and middle-income households to Covid-19 in Africa were mediated by the state through various means including direct cash transfers, food distribution, and distribution of rural agricultural produce to urban areas, in response to the social reproduction crisis that the pandemic precipitated. Taking the relationship between the state and household as its focus, this article reflects on the social and political questions emerging at the conjuncture of social provisioning and economic collapse. Central to these concerns is the structure of care economies in Africa and their relationship to the capitalist state.
Keywords: Covid-19; Care economy; State; Land; Gendered labour